Profiling the Millennial Visitors of the Smart Museum and Satisfaction of Visit: A Case Study of the Borneo Culture Museum, Sarawak Malaysia - Noralisa Ismail; Ahmad Puad Mat Som, Mohd Hafiz Hanafiah (Information Management and Business Review, 2025)
The pandemic has shifted museums to a new paradigm in which technology plays an increasingly important role in museum operations. More museums are investing in technology installations to give visitors a more distinctive and meaningful experience. Concerning technology, millennials (also called Generation Y) are an important market segment for museums. The increasing number of millennials visiting museums requires the related stakeholders to understand the millennial visitors' profile to serve them better. Hence, the purpose of this study is to assess the profile of Millennial visitors of the smart museum and investigate the role of technology in visitors’ satisfaction. This study employed five trained enumerators to approach the millennial visitors at the study location, the Borneo Culture Museum in Kuching, Sarawak.  The descriptive analysis was used to achieve the first objective followed by the simple linear regression for the second objective. The findings include demographic background, types of visits, source of information about the museum, travel companion, motivation to visit, time spent inside the exhibition galleries and the influence of technology on visitors’ satisfaction. The findings will be helpful as an addition to the existing knowledge of the museum research and can aid the future study in extending the study related to the millennial generation and the smart museum.